Eruptive lichen planus, a marker of metabolic syndrome - Gopalan Geetharani; Sundararaj Sumithra; Sendurpandian Devaprabha; Rajagopalan Kothandaramasamy (Wolters Kluwer Medknow Publications, 2019)
Background: Chronic inflammatory diseases take an important place in dermatology and their effects range from mild itching to grave metabolic complications. In psoriasis, association with metabolic syndrome (MS) has been proved in many studies. Chronic inflammation is a trigger of MS, and in turn, the components of MS, namely obesity and dyslipidemia, promote a pro-inflammatory milieu. Thus, chronic inflammation causes MS and vice versa. Hence, the study focuses on association of MS with lichen planus (LP), another chronic inflammatory disease. Aim: The aim of this study is to find the association of MS with all variants of LP. Materials and Methods: An observational study for MS in all patients with LP who attended skin outpatient department (OPD) for 6 months from February 2016. International Diabetes Federation criteria 2005 were used. The confounding variables of MS such as smoking, alcohol, and physical activity were assessed for its significance in the association of LP with MS. Results: Out of 113 cases, 21 cases were found to be associated with MS. Among them, 8 cases (38.09%) were of eruptive LP, which showed significant association with MS when compared to other variants. MS cases were significantly high in females and in the age group of 41-50 (57.1%). Due to unequal distribution of smoking and alcohol habits, they were not taken into account for analysis. Physical activity had no significant association with MS in our study population. Waist circumference (WC) being the mandatory criterion in all variants associated with MS, dyslipidemia was the next frequently encountered criteria except in eruptive LP. High BP was less commonly noted criteria. Conclusion: Eruptive LP showed significant association with MS. Further studies with large sample size in each variant and control group are needed to confirm it which are the limitations in our study.